Price and volatility transmission from international to domestic food and fertilizer markets in Central America - Hernandez, Manuel A.; Ceballos, Francisco; Berrospi, Maria Lucia; Perego, Viviana M. E.; Brown, Melissa; Lopez, Elena Mora (Wiley, 2026)
Recent global shocks have triggered sharp spikes in international food and fertilizer prices, raising concerns about their domestic impacts. This study examines the extent to which international price levels and volatility are transmitted to domestic food and fertilizer markets in seven Central American countries. We follow a multivariate GARCH approach using monthly data over the period 2000–2024. While results vary by country and commodity, we find overall low to moderate elasticities of price transmission in levels, but a stronger degree of volatility transmission in the very short term (1-month). Interestingly, price transmission tends to strengthen after 3 months, whereas volatility transmission is more short-lived and appears to dissipate. The co-movement between international and domestic prices shows no apparent trend over time and lacks consistency across countries and commodities following major global events. Back-of-the-envelope simulations of higher international food and fertilizer prices suggest modest, though non-negligible, impacts on local consumer and producer welfare.